L' album codé: un outil d'apprentissage des genres? - Hamaide-Jager, Eléonore (Ondina - Ondine, 2020)
This article examines picture books based on visual codes that contain no text apart from the title and the caption, as it is the case in the works of Warja Lavater, Sonia Chaine and Adrien Pichelin. We will study their reception as picture books and/or as tales and assess the impact they have on pupils. These book objects are not easy to read and require general knowledge to decipher the complexity of the characters and understand the allusion to fairy tales. The visual coding of other tales invite on the other hand to follow the picture book’s specificities to give meaning to the illustrations and to propose an enlightening iconographic reading. We will also explore the different types of expertise reading these picture books require.